Regime pluviométrico e estratégias de manejo sustentável no cultivo do feijão-caupi - Souza, Melina da Silva de (2023)
The analysis of climate elements and factors constitutes a basic condition for the implementation of cropping systems, mainly in the Brazilian semi-arid region, since they fundamentally impact agricultural production systems in a rainfed regime. In this region, the rainfall regime changes annually, ranging from very dry to very rainy. In addition, during the rainy season the distribution of precipitation occurs irregularly in time and space, resulting in consecutive dry days (dry spell). The dry spells reduce soil moisture and affect the growth and yield of temporary crops such as cowpea. In order to reduce the effects of dry spells, it is recommended to adopt conservationist practices such as mulching and organic fertilization, strategies tend to improve infiltration and water retention in the soil. Given the above, the objective was to quantify the occurrence and spatial distribution of dry spells according to the annual variability of rainfall in Ceará and thus develop agricultural management strategies to mitigate the water deficit. In order to understand the pattern of dry spells according to the rainfall regime, rainfall data from 1990 to 2019 were used for the 184 municipalities in Ceará, where the dry spells were counted and grouped according to duration. With the information maps were created using Ordinary Kriging in QGIS. To find solutions in order to reduce the negative influence of the climate on the cultivation of cowpea, an experiment was installed in Pentecoste - CE, in which the use of mulch and organic fertilization in the very dry, dry, normal and rainy water scenario was evaluated and its effects on soil moisture and cowpea production parameters. In the results it was obtained that in Ceará over the course of 30 years, the presence of 39,382 dry spells was recorded, which varied in quantity and intensity according to the rainfall regime. The Sertão Central and Sertão de Inhamuns region was the most affected by the climate, with the lowest precipitation values, the highest presence of long summers and low bean yields, especially in very dry and dry regimes. Given the situation, the use of mulch proved to be efficient to mitigate the effects of low water volume and poor distribution of rainfall in the most severe scenarios, helping to maintain soil moisture in periods of drought and guarantee the development of the crop. In addition, mulching and organic fertilization positively affected growth variables such as pod length and number of grains per pod. It is worth mentioning that the use of soil protection increased the yield in all water scenarios, where in the very dry regime the use of mulch ensured the productivity of 1,232 kg ha-1, representing an increase of 27% when compared to the control. In this way, simple techniques can reduce uncertainties and ensure bean productivity, especially in very dry and dry periods, and it is important to disseminate and encourage the use of these practices in rural areas by farmers.